2008
DOI: 10.1371/journal.pone.0002733
|View full text |Cite
|
Sign up to set email alerts
|

Differential Interactions of the Autonomous Pathway RRM Proteins and Chromatin Regulators in the Silencing of Arabidopsis Targets

Abstract: We have recently shown that two proteins containing RRM-type RNA-binding domains, FCA and FPA, originally identified through their role in flowering time control in Arabidopsis, silence transposons and other repeated sequences in the Arabidopsis genome. In flowering control, FCA and FPA function in the autonomous pathway with conserved chromatin regulators, the histone demethylase FLD and the MSI1-homologue FVE, a conserved WD-repeat protein found in many chromatin complexes. Here, we investigate how the RRM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 40 publications
1
66
0
2
Order By: Relevance
“…nfc101/nfc102 and TEs FVE and MSI5 are required for silencing of some Arabidopsis TEs and genomic repeats (Bäurle and Dean, 2008;Gu et al, 2011). Accordingly, we assessed whether the transcript level of maize TEs was affected in nfc101/nfc102 downregulation lines.…”
Section: Nfc101/nfc102 and Zcn8mentioning
confidence: 99%
See 1 more Smart Citation
“…nfc101/nfc102 and TEs FVE and MSI5 are required for silencing of some Arabidopsis TEs and genomic repeats (Bäurle and Dean, 2008;Gu et al, 2011). Accordingly, we assessed whether the transcript level of maize TEs was affected in nfc101/nfc102 downregulation lines.…”
Section: Nfc101/nfc102 and Zcn8mentioning
confidence: 99%
“…FVE activity is not limited to flowering regulation. Indeed, FVE is involved in coldinducible gene expression (Kim et al, 2004) and modulates silencing of transposable elements (TEs) and repeats, acting as an effector of the RNA-directed DNA methylation (RdDM) pathway (Bäurle and Dean, 2008;Gu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We have found that FRI does not disrupt the recruitment of FLD (or FLD-containing corepressor complex) to FLC chromatin but may partially disrupt FLD function. Because the AP genes FCA and FPA mainly function through FLD to repress FLC expression Baurle and Dean, 2008), a functional FRI may also disrupt the FLC repression mediated by these two genes. Taken together, our study suggests that FRI may play a dual role in the H3K4 trimethylation of FLC chromatin, namely, enriching an H3K4 methyltransferase complex and compromising H3K4 demethylation at FLC, to upregulate FLC expression and thus establish the winter-annual growth habit.…”
Section: Fri-mediated Wdr5a Enrichment At the Flc Locusmentioning
confidence: 99%
“…Arabidopsis thaliana fld-1, fld-3 , fca-9 (Baurle and Dean, 2008), and FRI-Col (Lee et al, 1994) were described previously. The wdr5b mutant was isolated from the Versailles transformant collection (Samson et al, 2002).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation